On the solution of fractional Maxwell equations by Sumudu transform. - Kilicman, Adem; Gupta, V. G.; Shrama, Bhavna (Canadian Center of Science and Education, 2010)
In this paper, we introduce the Maxwell equations of time- fractional order in lossy media. We derive the solution of these equations by using Sumudu transform techniques.